Differences In The Effect Of The Combination Of Square Stepping And Gaze Stabilization With Square Stepping And Core Stability On Dynamic Balance In The Elderly - Muslimaini, Muslimaini; Mirawati, Dita; Mutnawasitoh, Asita Rohmah (Jurnal Riset Kesehatan, 2023)
Physiological changes in the elderly occur related to skeletal muscle changes and are related to the balance of the fall risk assessment. Therefore, researchers provide Square Stepping, Gaze stabilization, and Core stability exercise interventions to improve dynamic balance. Square stepping exercise is an exercise to improve lower extremity functional fitness. Gaze Stabilization is an exercise to improve balance by way of cooperation between the vestibular system and the visual system. While Core Stability is a special exercise intended to help improve abdominal and lumbo pelvic muscles in trunk stability. The purpose of the study was to determine the difference in the effect between the combination of Square stepping and Gaze stabilization exercise with Square stepping and Core stability exercise on improving dynamic balance in the elderly. This research is a quantitative study with a quasi experimental type of research. The sample amounted to 30 respondents with a purposive sampling technique. Measurement of dynamic balance using TUGT. The Square Stepping intervention was carried out 3 times a week for 4 weeks, Gaze Stabilisation was carried out 3 times a week for 4 weeks and Core Stability was carried out 2 times a week for 4 weeks. Based on the Mann-Whitney Test using the TUGT measurement instrument, a significance value of 0.034 (p <0.05) was obtained. The results of this study indicate that there is a difference in the effect between giving square stepping and gaze stabilization with square stepping and core stability exercise on improving dynamic balance in the elderly.